Noninvasive Intracranial Pressure Estimation With Transcranial Doppler: A Prospective Observational Study. Issue 4 (October 2020) - Cardim, Danilo; Robba, Chiara; Czosnyka, Marek; Savo, Davide; Mazeraud, Aurelién; Iaquaniello, Carolina; Banzato, Erika; Rebora, Paola; Citerio, Giuseppe
Abstract : Background: Transcranial Doppler (TCD) ultrasonography has been described for the noninvasive assessment of intracranial pressure (ICP). This study investigates the relationship between standard, invasive intracranial pressure monitoring (ICPi ) and noninvasive ICP assessment using a simple formula based on TCD-derived flow velocity (FV) and mean arterial blood pressure values (ICPTCD ). Material and Methods: We performed a prospective observational study on 100 consecutive traumatic brain injury patients requiring invasive ICP monitoring, admitted to the Neurosciences and Trauma Critical Care Unit of Addenbrooke's Hospital, Cambridge, UK. ICPi was compared with ICPTCD using a method based on the "diastolic velocity-derived estimator" (FVd ), which was initially described for the noninvasive estimation of cerebral perfusion pressure but subsequently utilized for ICP assessment. Results: Median ICPi was 13 mm Hg (interquartile range: 10, 17.25 mm Hg). There was no correlation between ICPi and ICPTCD ( R =−0.17; 95% confidence interval [CI]: −0.35, 0.03; P =0.097). Bland-Altman analysis demonstrated wide 95% limits of agreement between ICPi and ICPTCD (−27.58, 30.10; SD, 14.42). ICPTCD was not able to detect intracranial hypertension (ICPi >20 mm Hg); the area under the receiver operating characteristic curve for prediction was 34.5% (95% CI, 23.1%-45.9%) with 0% sensitivity and 74.4% specificity for ICPTCD to detect ICPi >20 mm Hg. Conclusions: Using a formula based on diastolic FV, TCD is an insufficiently accurate method for the noninvasive assessment of ICP. Further studies are warranted to confirm these results in a broader patient cohort. Abstract : Supplemental Digital Content is available in the text.